The reporting on ERAS Compliance, Outcomes, and Elements Research (RECOvER) checklist: a joint statement by the ERAS® and ERAS® USA societies - Elias, Kevin M.; Stone, Alexander B.; McGinigle, Katharine; Tankou, Jo'An I.; Scott, Michael J.; Fawcett, William J.; Demartines, Nicolas; Lobo, Dileep N.; Ljungqvist, Olle; Urman, Richard D. (Springer, 2018)
Background: Enhanced Recovery After Surgery (ERAS) programs are multimodal care pathways designed to minimize the physiologic and psychological impact of surgery for patients. Increased compliance with ERAS guidelines is associated with improved patient outcomes across surgical types. As ERAS programs have proliferated, an unintentional effect has been significant variation in how ERAS-related studies are reported in the literature. Methods: To improve the quality of ERAS reporting, the ERAS® USA and the ERAS® Society launched an effort to create an instrument to assist authors in manuscript preparation. Criteria to include were selected by a combination of literature review and expert opinion. The final checklist was refined by group consensus. Results: The Societies present the Reporting on ERAS Compliance, Outcomes, and Elements Research (RECOvER) Checklist. The tool contains 20 items including best practices for reporting clinical pathways, compliance auditing, and formatting guidelines.